Pencapaian Self dan Wujud Persona melalui Mekanisme Pertahanan dalam Cerpen “Kenalilah Pembunuh Itu” karya Tawfiq al-Hakim - Diva Salsabila Anindita; Muhammad Luthfi Zuhdi (Jurnal Bahasa dan Sastra, 2023)
An individual's psychological responses to pressure and conflict may impact their thoughts and actions. The research aims to see how self-defense mechanisms may develop a 'Persona' to cover anxiety over pressure and fulfill the the objective of the 'Self,' as depicted in Taufiq al-Hakim's short story “Kenalilah Pembunuh Itu” in a collection of short stories entitled Arinî Allah which was first published in 1999. This study uses qualitative methods from the perspective of personality psychoanalysis of Persona and Self from Carl Jung and defense mechanisms from Sigmund Freud. The data identified were in the form of the forms of defense carried out by the defendant male character, the Persona that he showed to the public, and the achievement of Self in the form of the ultimate goal which became his redemption. The study's findings reveal how the male character accused in short stories uses his defense mechanism to protect himself from anxiety and feelings of guilt. From this process, the accused man manifested the personality of Persona and Self as self-exemption for feelings of guilt and disappointment over the justice that was questioned in his social environment